Comparison of the severity of periodontal disease in male smokers, betel chewers and non tobacco users in a rural community, in the Kandy district of Sri Lanka - Amarasena, H.D.N (My University, 1997)
The main objective of the present study was to determine the periodontal status of male smokers and betel chewers in a rural community in the Kandy district of Sri Lanka and compare it with that of male non tobacco users of the same community. Multiple linear regression analysis of data disclosed that both smokers and betel chewers had significantly higher levels of bacterial plaque than non tobacco users notwithstanding age, oral hygiene practices and socio -economics status. The gingival inflammation was significantly greater in betel chewers than in smokers and non tobacco users independent of age, oral hygiene and socio -economics factors. Moreover, periodontal pocket depths were significantly deeper in smokers than in betel chewer and non tobacco users regardless of oral hygiene and socio- demographic factors. However, there were no significant effects of smoking and betel chewing per se on loss of epithelial attachment when controlled for oral hygiene, age and socio - economic factors. Nevertheless the effect of the quantity of tobacco used per se on loss of attachment was statistically significant even after controlling for age, oral hygiene and socio- economic status